2021
DOI: 10.1101/2021.08.21.456841
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Limited evidence of a genetic basis for sex determination in the common creek chub, Semotilus atromaculatus

Abstract: 1AbstractSexual reproduction is almost universal in the animal kingdom; therefore, each species must have a mechanism for designating sex as male or female. Fish especially have a wide range of sex determining systems. While incompatible systems are thought to increase reproductive isolation, interspecific hybridization is common among groups such as cyprinid minnows, thus, studies such as this can provide insight into hybridization and evolutionary diversification of this clade. In the present study, we aimed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…For instance, in this special issue: Using a combination of short‐read and long‐read sequencing, Evans et al (2022) and Duhamel et al (2022) perform a chromosome‐scale genome assembly in the Marsabit clawed frog and anther‐smut fungi, respectively. These approaches allow the study of intra‐specific variation of sex chromosome divergence in the frog and reveal independent chromosomal rearrangement in the mating‐type chromosomes of the fungi. With short‐read WGS and the help of existing reference genomes, Sigeman et al (2022) investigate the translocation nature of a novel neo‐sex chromosome in Sylvivoidea songbirds, whilst Rovatsos et al (2022) reveal a XX/XY sex determination system in a blind lizard and further identified a novel combination of homologous genes using the chicken X chromosome as reference. With short‐read whole‐genome pooled sequencing, Ansai et al (2022) and Jeffries et al (2022) investigate the sex‐determining regions and sex chromosome turnover across closely related fish taxa. With RAD‐seq, Keating et al (2022) and Meuser et al (2022) perform analysis in multiple individuals per sex to investigate possible sex‐determining regions and infer sex chromosome turnovers. …”
Section: Theme 1: Genomics and Methodological Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in this special issue: Using a combination of short‐read and long‐read sequencing, Evans et al (2022) and Duhamel et al (2022) perform a chromosome‐scale genome assembly in the Marsabit clawed frog and anther‐smut fungi, respectively. These approaches allow the study of intra‐specific variation of sex chromosome divergence in the frog and reveal independent chromosomal rearrangement in the mating‐type chromosomes of the fungi. With short‐read WGS and the help of existing reference genomes, Sigeman et al (2022) investigate the translocation nature of a novel neo‐sex chromosome in Sylvivoidea songbirds, whilst Rovatsos et al (2022) reveal a XX/XY sex determination system in a blind lizard and further identified a novel combination of homologous genes using the chicken X chromosome as reference. With short‐read whole‐genome pooled sequencing, Ansai et al (2022) and Jeffries et al (2022) investigate the sex‐determining regions and sex chromosome turnover across closely related fish taxa. With RAD‐seq, Keating et al (2022) and Meuser et al (2022) perform analysis in multiple individuals per sex to investigate possible sex‐determining regions and infer sex chromosome turnovers. …”
Section: Theme 1: Genomics and Methodological Advancesmentioning
confidence: 99%
“…The authors also point out that this duplicate AmhY represented the second independent duplication and recruitment of Amh as a sex‐determining gene, suggesting convergent evolution in two stickleback lineages. In a small minnow, the common creek chub, Meuser et al (2022) find almost zero sex‐linked markers with a RAD‐seq approach, providing insights into the limitations of this technique for species with poorly differentiated sex chromosomes. Applying a similar RAD‐seq pipeline, Keating et al (2022) successfully identify male‐specific markers in a banded gecko, suggesting the presence of a XX/XY sex chromosome system.…”
Section: Theme 4: Detection Of Sex‐determining Genes and Sex Chromoso...mentioning
confidence: 99%